Analisis Dampak Sosial Ekonomi Pengembangan Objek Wisata Labuhan Mangrove Pada Masyarakat Sekitar Dalam Persepektif Hifdzul Mal Dan Hifdzul Din - Muhammad Pondi; Dahruji Dahruji (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The Labuhan Mangrove Forest Education Labuhan is located in Labuhan Village, Ten District, Bangkalan Regency. The Labuhan Mangrove Forest area is actually a former pond area that was converted into a mangrove conservation area, then developed into a mangrove educational park by mangrove farmer groups as a tourist attraction or educational park, where this mangrove park is located. built by pertamina and managed together with the local community, this study aims to determine the impact of mangrove tourism on the socio-economic environment of the surrounding community which is reviewed from the perspective of hifdzul mal hifdzul din. The method used is a qualitative research method, where the source of data is through observation techniques which are strengthened by documentation and interview techniques with the manager of the mangrove harbor tour and the community around the tour and some other literature. This research has the goal that the existence of mangrove harbor tours can have a good impact and benefits for the surrounding community. Where people can trade and work (parking management) in tourist areas, these tours can increase income. From the results of the work and the results of trading, the community re-manages the results of their trade, used for their daily needs for food and the needs of children to go to school with halal results in accordance with God's commands, accept his orders and stay away from his prohibitions. Protecting children from work that is clear and lawful as well as saving and helping each other so that they can lighten the burden on others, such as giving alms according to the concept of hfdzul mal (safeguarding assets) where in protecting one's assets one must maintain and guard the assets owned so as to avoid things negative which is contrary to sharia